Analisis Kesulitan Belajar Siswa Dalam Menyelesaikan Soal Pecahan Desimal Kelas V SD Negeri Kauman Blora - Septina Indra Budiarti; Veryliana Purnamasari; Sunan Baedowi (STKIP Andi Matappa Pangkep, 2022)
Learning mathematics is still considered a difficult and unpleasant subject for students. Not infrequently many students are still unable to learn mathematics, because they think that learning mathematics is difficult. understand students when understanding the concept of destruction, making students feel difficult in working on problems related to the material This research uses a qualitative research approach. by using data collection techniques in the form of tests, observations, questionnaires / questionnaires, interviews, and documentation. The data analysis uses data collection, data reduction, data presentation, drawing conclusions. The results of the study in the form of learning difficulties in solving problems of destruction experienced by class V SDN Kauman Blora include: (1) difficulty understanding the problem by 11.6% (2) difficulty carrying out plans by 11.4% (3) difficulty understanding the problem by 20, 2% (4) difficulties in planning solutions by 21.1% (5) difficulties in implementing plans 15.1% (6) difficulties in looking back 14%. In addition, it is also influenced by several factors that cause learning in solving problems for fifth grade students at SDN Kauman Blora consisting of physical health factors, student motivation factors, environmental factors, teacher teaching style factors and infrastructure factors in schools.